Upaya Pencegahan Stunting Melalui Pemberian Makanan Sehat Dengan Implementasi Dapur Sehat dan Kakak Asuh Guna Memberantas Stunting di Desa Pagerejo Kabupaten Wonosobo - Yuwono, Cahyo; Luthfan Ramadhani, Imam Vermansyah; Prayogo, Rhamanda Bagas (Universitas Negeri Semarang, 2025)
Stunting, which indicates a disruption in child growth and development, is a significant issue in Wonosobo Regency, including in Pagerejo Village. The UNNES GIAT 9 KKN team has implemented a program during their Community Service (KKN) to address stunting, focusing on 26 children identified as experiencing stunting. This program includes conducting three healthy kitchen sessions with balanced nutrition menus and providing education on stunting and balanced nutrition to parents. Additionally, a mentoring program is in place to monitor the development of these children. Following the implementation of this program, progress has been observed in the 26 children with stunting, particularly in terms of weight, height, and head circumference.Through this outreach, it is hoped that mothers will gain a deeper understanding of stunting and become more aware of the importance of proper nutrition for their children. With increased knowledge and awareness, it is anticipated that the incidence of stunting in Pagerejo Village, Wonosobo Regency, will decrease, as children are the future generation. Moreover, attention to child nutrition and diet is expected to contribute to producing high-quality human resources in the future.